2020
DOI: 10.1109/tcds.2018.2876090
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Criticality of Gene Regulatory Networks in Morphogenesis

Abstract: Gene regulatory network (GRN)-based morphogenetic models have recently gained an increasing attention. However, the relationship between microscopic properties of intracellular GRNs and macroscopic properties of morphogenetic systems has not been fully understood yet. Here we propose a theoretical morphogenetic model representing an aggregation of cells, and reveal the relationship between criticality of GRNs and morphogenetic pattern formation. In our model, the positions of the cells are determined by spring… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…By casting the emergent dynamics at multiple scales in the circuit space, this approach brings us a step closer to closing the gap between the structure and the function of a complex dynamical system. In this regard, our method also contributes to the theory of complex systems by complementing and potentially generalizing existing approaches to characterizing canalization [ 88 ], control [ 92 ], collectivity [ 70 , 93 ], coarse-graining [ 94 , 95 , 96 ] and criticality in complex nonlinear dynamical systems [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…By casting the emergent dynamics at multiple scales in the circuit space, this approach brings us a step closer to closing the gap between the structure and the function of a complex dynamical system. In this regard, our method also contributes to the theory of complex systems by complementing and potentially generalizing existing approaches to characterizing canalization [ 88 ], control [ 92 ], collectivity [ 70 , 93 ], coarse-graining [ 94 , 95 , 96 ] and criticality in complex nonlinear dynamical systems [ 97 , 98 ].…”
Section: Discussionmentioning
confidence: 99%
“…Boolean networks were proposed by Stuart Kauffman as gene regulatory network models [ 25 , 26 , 27 ]. They have been extensively used in many areas including artificial life, robotics, and systems biology [ 28 , 29 , 30 , 31 , 32 , 33 , 34 ]. They consist of nodes and links, where nodes represent genes, and the links represent interactions between genes.…”
Section: Methodsmentioning
confidence: 99%
“…Comparing the attractors between the original and mutated networks, we classify the properties of biological networks [ 66 ]. Our classification is extended from the definition of robust and evolvable network in Aldana et al’s work [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…As mentioned in Introduction (Section 1), we have presented a new GRN-based morphogenetic model and revealed the role of the criticality of GRNs in morphogenesis [21,22]. To make our finding more solid from an evolutionary viewpoint, we included genetic perturbations occurring in real living organisms in our morphogenetic model.…”
Section: Perturbations To Grns and Robust And Evolvable Grnsmentioning
confidence: 99%
“…They all used a discrete space like Cellular Automata, which is not realistic as a model of morphogenetic processes. To investigate a potential role of criticality of GRNs at a multicellular level which is hard to uncover through the single-cell-level studies, we have recently proposed GRN-based morphogenetic systems operating in a continuous space and revealed that the criticality of GRNs facilitated the formation of nontrivial morphologies [21,22]. To make our finding more solid from an evolutionary viewpoint, in this study, we include an evolutionary process in our morphogenetic model by introducing genetic perturbations (e.g., mutations) to GRNs.…”
Section: Introductionmentioning
confidence: 99%